Effectiveness of Black Cumin (Nigella Sativa) Seed Extract as an Antibacterial Agent Against Mycobacterium Tuberculosis Using The Resazurin Microtiter Assay (REMA) Method - Laura Freitas Silva Ferreira; Nurul Wiqoyah; Tutik Kusmiati; Eko Budi Koendhori (Jurnal Locus Penelitian dan Pengabdian, 2026)
Tuberculosis remains a major global health problem caused by Mycobacterium tuberculosis. The rising prevalence of multidrug-resistant tuberculosis and the adverse effects associated with prolonged first-line therapy like rifampicin, highlight the need for alternative or adjunctive treatments. Nigella sativa, a medicinal plant rich in bioactive compounds, has attracted considerable attention because of its antimicrobial, antioxidant, anti-inflammatory, and immunomodulatory properties, which are primarily attributed to its major active compound, thymoquinone. This study aimed to determine the antimicrobial activity and minimum inhibitory concentration of Nigella sativa seed extract against Mycobacterium tuberculosis using the resazurin microtiter assay method. A true experimental study was conducted using the H37Rv strain of Mycobacterium tuberculosis. A methanolic extract of Nigella sativa seeds was prepared using the maceration method. Antibacterial activity was assessed using the resazurin microtiter assay (REMA) after 10 days of incubation. Bacterial growth inhibition was determined through visual observation of resazurin color change and confirmed using a microplate reader at 630 nm. Wells remaining blue indicated inhibition, whereas pink indicated growth. Rifampicin and sterile water were included as positive and negative controls respectively to validate experimental conditions and assay performance consistency throughout the study. Nigella sativa seed extract demonstrated antimicrobial activity with a minimum inhibitory concentration of approximately 0.125 mg/mL (31-62 µg/mL), indicated by the absence of color change and supported by lower absorbance values at 630 nm. Rifampicin showed inhibitory activity at significantly lower concentrations 0.125µg/mL, confirming its higher antimicrobial potency. Nigella sativa seed extract exhibits measurable antibacterial activity against Mycobacterium tuberculosis.